Effects of long-term no-tillage systems with different succession cropping strategies on the variation of soil CO2 emission - de Araújo Santos, Gustavo André [UNESP]; Moitinho, Mara Regina; de Oliveira Silva, Bruna [UNESP]; Xavier, Clariana Valadares [UNESP]; Teixeira, Daniel De Bortoli; Corá, José Eduardo [UNESP]; Júnior, Newton La Scala [UNESP] (Elsevier, 2019)
The optimization of conservationist production systems, whose goal is to increase carbon stocks and reduce greenhouse gas emissions, is considered one of the greatest challenges faced by agriculture nowadays. Therefore, this study aimed to assess the variation of soil CO2 emission (FCO2) and its relationship with soil attributes under long-term no-tillage systems with different successions of summer and winter crop sequences. Treatments consisted of combinations of three summer and two winter crop sequences. Summer sequences were maize monocrop (MM), soybean monocrop (SS), and soybean-maize intercrop (SM), while winter crops were crotalaria and maize. FCO2 showed no difference among summer sequences (p > 0.05). For winter crops, however, the soil under crotalaria crop residues presented higher FCO2 values (1.03 ± 0.027 μmol m−2 s−1) when compared to that under maize crop residues (0.94 ± 0.027 μmol m−2 s−1). Soil moisture presented the greatest influence on the temporal variation of FCO2, being correlated in the summer sequences MM (r = 0.79; p < 0.0001) and SS (r = 0.70; p = 0.002), as well as in the winter crops crotalaria (r = 0.78; p < 0.0001) and maize (r = 0.66; p = 0.005). In the Oxisol under no-tillage for >14 years, the spatial variation of FCO2 was explained by the soil physical attributes total porosity, macroporosity, microporosity, and soil temperature. The soil under crotalaria crop residues as a winter crop had an improvement in soil physical attributes, leading to a more aerated environment and hence a higher CO2 production process. However, the winter crops crotalaria (38.65 ± 0.08 Mg ha−1) and maize (38.14 ± 0.09 Mg ha−1) also provided a higher carbon stock on this tropical soil. Maize monocrop (41.13 ± 0.11 Mg ha−1) as a summer crop under no-tillage system also promoted higher carbon stocks on this tropical soil. A strategy to optimize no-tillage systems in terms of FCO2 reduction and increase in soil carbon stock is related to the adoption of crop cultivation that includes legumes and grasses under intercropping and succession. Therefore, our results suggested that the summer sequences used in this study might contribute to reducing FCO2 and that both winter crops influenced the increased soil carbon stock.
Keywords: Climate-smart-agriculture; Soil carbon storage; Soil respiration; Soil structure; Tropical soil